ANALYSIS OF DETERMINING FACTORS ON CUSTOMER LOYALTY AT STARBUCKS CAFE - Tony Ruswandy; Jasmine Angela; Rosinta Romauli Situmeang; Hendra Jonathan Sibarani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
In the food and beverage industry, customer loyalty is a valuable asset. Amidst intense competition, particularly in the café segment, companies need to understand customer expectations to maintain loyalty. Starbucks, as a market leader, employs a comprehensive strategy to build strong relationships with customers, including analyzing the impact of location, price, and brand image on loyalty. This study makes use of a quantitative method with a multiple linear regression model, involving a sample size of 75. The results indicate that location has a positive and significant effect on customer loyalty, supporting the first hypothesis. Price also has a positive and significant impact on customer loyalty, validating the second hypothesis. Brand image positively and significantly influences customer loyalty, confirming the third hypothesis. Furthermore, the variables of location, price, and brand image collectively have a positive and significant effect on customer loyalty.